Dying Hungry: Nazi Ideology and the Pragmatism behind Starvation in Implementing the Final Solution - Feferman, Kiril (East/West)

(untitled) (Canadian Institute of Ukrainian Studies University of Alberta, 2021)
German theories and policies regarding the relationship between food and Jewish citizens of eastern Europe served as an important foundation of the Nazis’ Judenpolitik during the Holocaust (1933-45). The mass starvation of Jews in German-dominated Europe was the result of a carefully calculated policy to make the Jews pay for a long list of misfortunes they had allegedly inflicted on the Germans. This policy evolved from a highly restrictive and discriminatory approach toward German Jews, which unfolded against a backdrop of harsh food policies applied to the local non-Jewish population.